A one-year prospective study of morbidity and mortality in first year following a hip fracture among the elderly patients - Penchalaih, Alam; Vijayanand, Addanki (International Journal of Research in Orthopaedics, 2020)
Background: Hip fractures are one of the most commonest and devastating injuries among the geriatric population. Increasing age, cognitive impairment and higher ASA scores are significantly associated with mortality among the geriatric age group. The objective of this study to evaluate the incidence and causes of morbidity and mortality associated with fracture of the hip in first year after the injury among the elderly population. Methods: A eighteen months prospective study at Narayana Medical College was conducted among patients aged >60 years treated for fracture of hip by arthroplasty and internal fixation. The cases were followed up for one year and mortality and morbidity were evaluated. Associated medical co morbidities were noted for all the cases in the study. Statistical analysis was carried out with IBM SPSS 24.0 and Stata 14 software. Results: In the study, 76 cases with M:F ratio of 7:12 and mean age of 63.21±1.4 years were included. Cardio vascular disease and anaemia were common co morbidities. Total mortality percentage in the present study after one year of follow up was 31.58%. Mean age of the cases with death in arthroplasty group was 71 years and 69 years in internal fixation group. Associated medical conditions had a direct relationship with mortality on the patients following surgery for fracture of the hip. Conclusions: Hemiarthroplasty for fracture of the neck and Internal fixation using dynamic hip screw for trochanteric fracture are still good options in the elderly. Proper post-operative management and follow up management for medical co morbidities provide better functional outcome and good results.